2022
DOI: 10.1111/1471-0528.17299
|View full text |Cite
|
Sign up to set email alerts
|

Levels of anxiety in women aged ≥45 years undergoing diagnostic large loop excision of the transformation zone: A longitudinal study

Abstract: Objective: To measure anxiety levels in women aged ≥45 years undergoing diagnostic large loop excision of the transformation zone (LLETZ) at the first colposcopy visit.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…Referral for colposcopy is a known harm of screening as it can lead to psychological distress and anxiety [29][30][31]. However, a previous study has found lower anxiety levels in older women undergoing colposcopy and treatment (median age 67.7 years) compared to women aged 23-50 [32,33]. Additionally, a recent Danish qualitative study demonstrated that older post-menopausal women preferred diagnostic LEEP over continued surveillance, even if this would result in increased risk of overtreatment [34].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Referral for colposcopy is a known harm of screening as it can lead to psychological distress and anxiety [29][30][31]. However, a previous study has found lower anxiety levels in older women undergoing colposcopy and treatment (median age 67.7 years) compared to women aged 23-50 [32,33]. Additionally, a recent Danish qualitative study demonstrated that older post-menopausal women preferred diagnostic LEEP over continued surveillance, even if this would result in increased risk of overtreatment [34].…”
Section: Discussionmentioning
confidence: 99%
“…From April 17 through December 31, 2017, women born before 1948 (i.e., aged 69 + at that time) were invited for one additional HPV screening test [4,15]. HPV DNA testing was performed using the clinically validated COBAS 4800 assay (Roche Diagnostics), which allows for individual detection of HPV16 and HPV18, and pooled detection of 12 other high-risk HPV types (31,33,35,39,45,51,52,55,56,58,66,68). Women were referred directly for colposcopy if they were positive for HPV16 and/or HPV18, or if they were positive for other HPV types than HPV16/18 and had atypical squamous cells of undetermined significance or worse (ASC-US +) on reflex cytology.…”
Section: Methodsmentioning
confidence: 99%
“…10 TZ type 3 poses a problem during colposcopies: studies revealed inadequate colposcopy in up to 67% of postmenopausal women (mean age: 62 years), mostly due to TZ type 3. 8 9 11 This challenge may result in prolonged follow-up involving repeated colposcopies to obtain representative biopsies, causing psychological distress and anxiety among patients, [12][13][14] as well as an increased risk of missing disease in the cervical canal. 8 11 This risk is considerable and is supported by a Danish study among screen-positive older women (median age 67.7 years) with TZ type 3 showing that more than half (54.5%) of the CIN grade 2 or higher (CIN2+) (CIN2, CIN3/Adenocarcinoma in Situ (AIS), cancer) cases detected in the cone biopsy were missed by colposcopyguided biopsies.…”
Section: Strengths and Limitations Of This Studymentioning
confidence: 99%